2023
DOI: 10.2478/pcssr-2023-0004
|View full text |Cite
|
Sign up to set email alerts
|

Middle-Aged Women’s Perceptions and Experiences of Physical Activity: A Grounded Theory Approach

Abstract: Effective public health interventions require an understanding of why people engage in or abstain from physical activity. This study aimed to design a model of physical activity for middle-aged Iranian women. The research was conducted using the systematic approach of grounded theory. Data analysis was performed through continuous „questioning” and „comparison.” Semi-structured interviews were conducted with 35 middle-aged women (aged 40 to 65) who regularly engaged in physical activity to achieve theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Women's limited leisure time compared to men is primarily a result of time constraints and financial limitations (11). Numerous studies have demonstrated that various individual environmental, social, and physical activity factors contribute to one's perception of the advantages and disadvantages associated with regular physical activity (12)(13)(14)(15)(16)(17)(18). Additionally, positive and negative cognitive elements play a crucial role in determining whether individuals engage in consistent physical activity or not.…”
mentioning
confidence: 99%
“…Women's limited leisure time compared to men is primarily a result of time constraints and financial limitations (11). Numerous studies have demonstrated that various individual environmental, social, and physical activity factors contribute to one's perception of the advantages and disadvantages associated with regular physical activity (12)(13)(14)(15)(16)(17)(18). Additionally, positive and negative cognitive elements play a crucial role in determining whether individuals engage in consistent physical activity or not.…”
mentioning
confidence: 99%